Evidence of a Relationship between Adult Attachment Variables and Appraisals of Chronic Pain - Pamela J Meredith; Jenny Strong; Judith A Feeney (Pain Research and Management)
OBJECTIVE: Although threat and challenge appraisals of pain have been linked to both the acute and laboratory-induced pain experience, these appraisals have not yet been explored in relation to chronic pain. In addition, although attachment theory has been separately linked to the chronic pain experience and to responses to perceived threat, it has not been explored in the context of threat and challenge appraisals of chronic pain. The present paper addresses these two main goals.